2022
DOI: 10.7189/jogh.12.05027
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of demographic data, clinical signs, comorbidities, and outcomes according to the race in hospitalized individuals with COVID-19 in Brazil: An observational study

Abstract: Background Brazil is a multiracial country with five major official races: White, Black, individuals with multiracial backgrounds, Asian, and Indigenous. Brazil is also one of the epicentres of the Coronavirus Disease (COVID)-19 pandemic. Thus, we evaluated how the races of the Brazilian population contribute to the outcomes in hospitalized individuals with COVID-19, and we also described the clinical profile of the five official Brazilian races. Methods We performed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Brazil is one of the most affected countries by COVID-19, being the fifth in number of cases (37.4 million) and second in number of deaths (700,000) ( Coronavírus Brasil, 2023 ). The main epidemiological risk factors for severity and death in the Brazilian population are in accordance with worldwide studies and include primarily age over 60 years old, and to a much lower extent, lower socioeconomic status, male gender, and presence of comorbidities ( Zhang et al , 2020a ; Sansone et al, 2022 ). In addition to these, Sansone et al (2022 ) analyzed 585,655 Brazilian hospitalized patients and identified that Native Americans, Afro-descendants, and multiracial background individuals were slightly more likely to die from COVID-19, when compared with white Brazilians, with odds 1.91 (95% CI = 1.70-2.15), 1.43 times (95% CI = 1.39-1.48), and 1.36 (95% CI = 1.34-1.38), respectively.…”
Section: Introductionsupporting
confidence: 68%
“…Brazil is one of the most affected countries by COVID-19, being the fifth in number of cases (37.4 million) and second in number of deaths (700,000) ( Coronavírus Brasil, 2023 ). The main epidemiological risk factors for severity and death in the Brazilian population are in accordance with worldwide studies and include primarily age over 60 years old, and to a much lower extent, lower socioeconomic status, male gender, and presence of comorbidities ( Zhang et al , 2020a ; Sansone et al, 2022 ). In addition to these, Sansone et al (2022 ) analyzed 585,655 Brazilian hospitalized patients and identified that Native Americans, Afro-descendants, and multiracial background individuals were slightly more likely to die from COVID-19, when compared with white Brazilians, with odds 1.91 (95% CI = 1.70-2.15), 1.43 times (95% CI = 1.39-1.48), and 1.36 (95% CI = 1.34-1.38), respectively.…”
Section: Introductionsupporting
confidence: 68%
“…After excluding studies which contained duplicate patient data, 77 studies comprising over 200,000,000 confirmed COVID-19 cases were included. 4 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , ...…”
Section: Resultsmentioning
confidence: 99%
“…In the multivariate analysis, the male sex was a risk factor for the mortality of people infected by COVID-19 and age, with older ages being related to a worse prognosis, in agreement with other studies found in the literature, including a meta-analysis of 212 studies and 281,461 individuals ( 35 ). Indigenous peoples were more prone to die from COVID-19 than other races, followed by multiracial background patients ( Pardos ) and the Black race, and then by White patients ( 19 , 33 , 36 , 37 ). Interestingly, our data demonstrated a relationship between education level and mortality for COVID-19 infections, in which the higher the patients’ education level, the lower the mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained the data between 17 February 2020 and 10 October 2021. In addition, the dataset used in the present study was published and validated in other studies ( 18 33 ).…”
Section: Methodsmentioning
confidence: 95%